2022
DOI: 10.3390/s22062208
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Novel MediPost Mobile Posturography Device in the Assessment of Patients with a Unilateral Vestibular Disorder

Abstract: Balance disorders are a growing problem worldwide. Thus, there is an increasing need to provide an inexpensive and feasible alternative to standard posturographic platforms (SP) used for the assessment of balance and to provide a possible solution for telemonitoring of patients. A novel mobile posturography (MP) MediPost device was developed to address these issues. This prospective study used a Modified Clinical Test of Sensory Interaction on Balance to evaluate healthy individuals and patients with a unilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
6
1
Order By: Relevance
“…The instrumental measurement performed using MediPost mobile posturography localized at the L5 level, assessed postural stability in different conditions where the noted grade of improvement varied, as stated in the literature [ 13 , 39 , 40 , 41 ]. The results of condition 4 (standing on foam, eyes closed) were statistically significant for all MediPost measures, which is consistent with other studies [ 5 , 29 , 42 ]. The results of condition 1 (firm surface, eyes open) and condition 2 (firm surface, eyes closed) are clinically unsatisfactory.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The instrumental measurement performed using MediPost mobile posturography localized at the L5 level, assessed postural stability in different conditions where the noted grade of improvement varied, as stated in the literature [ 13 , 39 , 40 , 41 ]. The results of condition 4 (standing on foam, eyes closed) were statistically significant for all MediPost measures, which is consistent with other studies [ 5 , 29 , 42 ]. The results of condition 1 (firm surface, eyes open) and condition 2 (firm surface, eyes closed) are clinically unsatisfactory.…”
Section: Discussionsupporting
confidence: 92%
“…Postural stability was measured using the portable, battery-powered MediPost system with one sensor mounted on the trunk at the L5 level [ 16 ]. Mobile posturography allows for a more direct measurement of COM, which is strongly correlated with the center of pressure (COP) [ 29 ]. The system consisted of the ESP32 system, a Wi-Fi radio module, and the tri-axis inertial measurement unit (IMU; STMicroelectronics LSM9DS1) based on a microelectromechanical system (MEMS) that included an accelerometer, a gyroscope, and a magnetometer (manufactured by University of Technology, Lodz, Poland).…”
Section: Methodsmentioning
confidence: 99%
“…All of the studies report COP measurements from the force plate, with the majority using COP velocity or sway area as the main output parameter. In comparison, the study by Marchetto et al [ 16 ] analyzed the head position with angular velocity values, as in other studies using body-mounted sensors of posture [ 36 ]. The study protocols were different across the manuscripts, as were the VR environments; therefore, a meta-analysis of posturography parameters and VR influence on stability was not attempted in this manuscript.…”
Section: Resultsmentioning
confidence: 99%
“…The study proves a significant effect of the increasing visual disturbance in the virtual environment on sway parameters. We chose angular velocity as the reference parameter, as in our previous research regarding wearable sensors and accelerometry 21 . We found that a static and stable virtual environment has little influence on angular velocity.…”
Section: Discussionmentioning
confidence: 99%